Negative Mental Health Factors in Children Orphaned by AIDS: Natural Mentoring as a Palliative Care - Onuoha, Francis N.; Serumaga-Zake, Philip A. E.; Nyonyintono, Rebecca M.; Bogere, Stephen M. (AIDS and Behavior, 2009)
The study examined the psychosocial mental health of some children whose parents died of AIDS (n = 373) in Uganda and South Africa. The design had 2 control groups: other-causes orphaned (n = 287), and non-orphaned (n = 290) children (grand mean age = 13.59, SD = 2.34). We utilized a battery of standardized psychosocial measures to estimate mental health in the groups. Natural mentoring relationship was estimated with the Ragins and McFarlin (J Vocat Behav 37:321–339, 1990) Mentor Role Instrument. Results indicated that AIDS-orphaned children showed highest negative, and lowest positive mental health factors in the 3 groups. Children in a mentoring relationship showed better mental health factors than those without a mentor. We ascribed the AIDS-orphaned children’s highest negative mental health condition to the incidence of higher double parental loss in the group, and suggested natural mentorship as a palliative care against negative mental health.
Keywords: Natural mentoring; Mental health; AIDS-orphaned children; Non-orphaned children